MODEL EVALUASI PEMBELAJARAN BERBASIS PROYEK UNTUK PEMBENTUKAN KARAKTER SISWA DI SDN 40/I BAJUBANG LAUT - Elmina Fitri; Muhammad Yatim; Beni liantori; Renda Melati; Kholisatun Nabila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Project-Based Learning (PjBL) is a learning model that positions students as the main subjects in the learning process through the completion of contextual, collaborative, and meaningful projects. This model is believed to be effective in developing higher-order thinking skills while simultaneously fostering students’ character development. However, the implementation of PjBL in elementary schools is often not supported by a comprehensive evaluation system, particularly in measuring students’ character formation. This study aims to provide an in-depth description of the project-based learning evaluation model in shaping the character of elementary school students at SDN 40/I Bajubang Laut. This research employed a qualitative approach using a descriptive method. The research subjects included teachers and students at SDN 40/I Bajubang Laut who implemented project-based learning. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing by applying source and technique triangulation. The results show that the PjBL evaluation model was implemented systematically through four main components, namely process evaluation, product evaluation, attitude (character) evaluation, and learning reflection. The character values developed among students include responsibility, cooperation, discipline, honesty, independence, and creativity. This evaluation model provides a comprehensive overview of students’ character development and supports the implementation of authentic assessment in elementary schools